2020
DOI: 10.1139/as-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Social-ecological changes and implications for understanding the declining beluga whale (Delphinapterus leucas) harvest in Aklavik, Northwest Territories

Abstract: Subsistence is the basis for food access for Inuvialuit in the western Canadian Arctic and has strong economic, dietary, and cultural importance. Inuvialuit harvest beluga whale (Delphinapterus leucas) from the eastern Beaufort beluga population during summer months within parameters established through co-management. Over the past thirty years there has been a dramatic decline in the number of beluga harvested by Inuvialuit from the community of Aklavik, NT. This paper investigates the potential drivers of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…In the context of peer review, participants discussed the importance of validating research findings, particularly those involving Indigenous Peoples and their knowledge, with the appropriate people and knowledge holders, especially Indigenous Knowledge (IK) holders. Determining effective processes for joint validation is an ongoing area of research (Gratani et al 2011;Wilson et al 2020;Worden et al 2020). These processes will likely vary on a case-by-case basis, but could include research teams composed of both science and IK experts; defining problems, goals, conceptual models, questions, and methods collaboratively; working on data collection and analysis; communicating results on a regular basis; consulting regularly with experts as part of the research team; and providing regular opportunities for feedback and input (Gearheard and Shirley 2007;Reed 2008;Pearce et al 2009;Grimwood et al 2012;Tengö et al 2014;Gérin-Lajoie et al 2018;Fox et al 2020;Pedersen et al 2020;Wilson et al 2020).…”
Section: Workhop Discussionmentioning
confidence: 99%
“…In the context of peer review, participants discussed the importance of validating research findings, particularly those involving Indigenous Peoples and their knowledge, with the appropriate people and knowledge holders, especially Indigenous Knowledge (IK) holders. Determining effective processes for joint validation is an ongoing area of research (Gratani et al 2011;Wilson et al 2020;Worden et al 2020). These processes will likely vary on a case-by-case basis, but could include research teams composed of both science and IK experts; defining problems, goals, conceptual models, questions, and methods collaboratively; working on data collection and analysis; communicating results on a regular basis; consulting regularly with experts as part of the research team; and providing regular opportunities for feedback and input (Gearheard and Shirley 2007;Reed 2008;Pearce et al 2009;Grimwood et al 2012;Tengö et al 2014;Gérin-Lajoie et al 2018;Fox et al 2020;Pedersen et al 2020;Wilson et al 2020).…”
Section: Workhop Discussionmentioning
confidence: 99%
“…For example, earlier ice breakup dates have resulted in belugas moving offshore earlier in the season and, compounded with rougher waters, has challenged hunter accessibility to belugas. Additionally, shifting socioeconomics, cultural practices, and loss of Elders has impacted beluga hunting practices (Worden et al, 2020). Deininger et al (2016) found that Antarctic tourism was inversely related to sea-ice coverage and speculated that the tourism industry would probably benefit from further seaice decline.…”
Section: Cultural Services and Societymentioning
confidence: 99%
“…9(1) page 2 of 55 Steiner et al: Sea-ice ecosystems and climate change boundaries; Tress et al, 2005) research for monitoring the impacts of climate change on polar ES. For instance, climate models are essential to project how the sea ice-ocean system may change under different climate scenarios, while Indigenous and local knowledge provides key insights into past changes and the implications of these changes for food security (e.g., changes in the appearance, health, distribution and abundance of harvested species; Gadamus, 2013;Harwood et al, 2015;Loseto et al, 2018a;Ostertag et al, 2018;Waugh, 2018;Worden et al, 2020), health, livelihoods, and culture, such as the loss of important sea-ice travel routes (ICC-Canada, 2008;Wilson et al, 2020). Collaborations between tourism organizations and research organizations can provide valuable input into spatial planning, conservation, and management efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Inuvialuit beluga hunters know the importance of respect for the beluga and continue cultural practices to take only what is needed and to share what is taken (Snow et al 2016). Despite the influences of climate and societal changes, hunters remain adaptable and rely on traditional skills and knowledge as well as values of cooperation, harmony and readiness (Collings et al 2018;Worden et al 2020). Hunting typically occurs in summer from small aluminum boats using harpoon-first methods to reduce struck-and-lost incidents, following local by-laws developed by Hunters and Trappers Committees (Day 2002;Harwood & Smith 2002;FJMC 2013).…”
Section: Inuvialuit Settlement Region Canadamentioning
confidence: 99%
“…Hunting typically occurs in summer from small aluminum boats using harpoon-first methods to reduce struck-and-lost incidents, following local by-laws developed by Hunters and Trappers Committees (Day 2002;Harwood & Smith 2002;FJMC 2013). Because beluga aggregate in large numbers in the Mackenzie Estuary/Delta in summer (Norton & Harwood 1986;Harwood et al 1996), hunters operate from summer whaling camps occupied by families from Inuvik and Aklavik or directly from the coastal community of Tuktoyaktuk (Waugh et al 2018;Worden et al 2020).…”
Section: Inuvialuit Settlement Region Canadamentioning
confidence: 99%